(untitled) (The Conference Hub, 2025)
This article analyzes the artistic expression of the motif of loneliness in the novel In the Woods (2007) by contemporary Irish writer Tana French. The study explores states of loneliness formed through trauma, the rupture between past and present, the loss of trust, and the process of self-awareness. The author interprets loneliness not merely as a psychological experience but as a philosophical one. The paper examines the elements of psychological realism, the system of symbols, and the artistic language techniques that reveal Tana French’s mastery in depicting the “inner forest” of the human soul.